Network Monitoring System - Irawati - Irawati (Universitas Islam Lamongan, 2020)
Traffic analysis and monitoring is needed to improve network service quality by using statistical analysis to obtain traffic characteristics. These statistics provide important signals about service quality and network throughput. Because of the heterogeneity of the bandwidth requirements of the traffic flow resulting from different applications, the resulting data can be used to determine the nature of IP traffic and to consider its characteristics. The first data type is data available from the Simple Network Management Protocol (SNMP) to the network nodes. The second is from IP current monitoring. The combination of these two data types provides a solid foundation for traffic analysis and monitoring. Which in this case we will apply to Mikrotik, dude applications, Internet of Things, Social Media, Website, SNMP, Probe, Zabbix, Security Information and Event Management (SIEM).Monitoring results are displayed in graphical form on the Network Monitoring System Web Application, so that users can find out more information. The network monitoring system developed is also very effective because the packet sent in one transaction is very small, which is 309 bytes when compared to the larger SNMP protocol. The results of the configuration of hardware and software with Zabbix NMS went well with the success of monitoring the service by detecting status changes on each host with 2 ownership statuses Ok and Warning. The availability value is influenced by the Uptime and Downtime of a device. The greater the Uptime value, the greater the availability value. The availability test results show that the application made has an error rate of 0% when compared with the calculation results. Using a network monitoring system using the SNMP protocol on the Mikrotik router and dude application, can help in network management